2013
DOI: 10.3109/03014460.2013.806590
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and beliefs toward biobehavioural research participation: voices and concerns of urban adolescent females receiving outpatient mental health treatment

Abstract: Background Biobehavioural research methodology can be invasive and burdensome for participants—particularly adolescents with mental illnesses. Human biological researchers should consider how methodological impositions may hinder adolescent research participation. However, literature on adolescent’s voices and concerns toward biobehavioural research participation is virtually non-existent. Aim This study was designed to determine adolescents’ perceptions of participation in research involving the collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 59 publications
1
56
0
Order By: Relevance
“…Specific suggestions from children and adolescents on improving assent processes included: for researchers to speak directly to children about research participation – not simply through their parents, ensuring written materials are written in a way that is appealing and understandable, and providing written information instead of using e-mails or websites (Brawner, Volpe, Stewart, & Gomes, 2013; Burke et al, 2005; Swartling et al, 2011; Swartling et al, 2014; Unguru et al, 2010). Specific tools that were demonstrated to enhance children’s and adolescents’ comprehension of research included an assent quiz, and a specific lesson on research rights (Bruzzese & Fisher, 2003; Chu, DePrince, & Weinzierl, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specific suggestions from children and adolescents on improving assent processes included: for researchers to speak directly to children about research participation – not simply through their parents, ensuring written materials are written in a way that is appealing and understandable, and providing written information instead of using e-mails or websites (Brawner, Volpe, Stewart, & Gomes, 2013; Burke et al, 2005; Swartling et al, 2011; Swartling et al, 2014; Unguru et al, 2010). Specific tools that were demonstrated to enhance children’s and adolescents’ comprehension of research included an assent quiz, and a specific lesson on research rights (Bruzzese & Fisher, 2003; Chu, DePrince, & Weinzierl, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The presence or absence of trust was perceived by children as a contributing factor to being involved in research, and also shaped their assessments of risk (Brawner et al, 2013; Traube et al, 2013; Woodgate & Edwards, 2010). Findings in the sample of articles suggested that children and adolescents are most willing to participate in research when they feel safe (Brawner et al, 2013; O’Reilly, Karim, Taylor, & Dogra, 2012; Swartling et al, 2011; Traube et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is evidence that webRDS may be advantageous for hidden youth populations for whom research participation may be stigmatizing (38). Racial, gender, and sexual minorities are especially vulnerable to medical mistrust, fear of authority, stigma, mistreatment, and exploitation (39-42). HIV research studies have struggled to sample adolescents due to HIV-related perceived stigma and negative social consequences (38).…”
Section: Discussionmentioning
confidence: 99%